2002
DOI: 10.1034/j.1600-0897.2002.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

The Expressions of Intracellular Cytokines in the Lymphocytes of Preeclamptic Patients

Abstract: These results suggest that in patients with preeclampsia there is Th1/Th2 imbalance, with predominant Th1 immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 50 publications
7
52
2
Order By: Relevance
“…The same results were reported later (Yoneyama et al, 2002;Ohkuchi et al, 2001;Rein et al, 2002). Further studies revealed that the cytokine profile in CD8 + T cells, NK cells and NKT cells also showed the Th1 type-cytokine predominant state (Darmochwal-Kolarz et al, 2002;Borzychowski et al, 2005).…”
Section: Th1/th2 Balance During Pregnancy and Preeclampsiasupporting
confidence: 80%
“…The same results were reported later (Yoneyama et al, 2002;Ohkuchi et al, 2001;Rein et al, 2002). Further studies revealed that the cytokine profile in CD8 + T cells, NK cells and NKT cells also showed the Th1 type-cytokine predominant state (Darmochwal-Kolarz et al, 2002;Borzychowski et al, 2005).…”
Section: Th1/th2 Balance During Pregnancy and Preeclampsiasupporting
confidence: 80%
“…On contrary to Th1 cells, the activation induced calcium response of the Th2 subset is not decreased compared with the non-pregnant state. The decreased activation of the Th1 subset and the lack of decrease in Th2 cells may partly be responsible for the well established Th2 skewness in healthy pregnancy (Darmochwal-Kolarz et al, 2002;Rein et al, 2002;Saito et al, 1999). Unlike in healthy pregnancy, we could not detect a difference in the AUC values of calcium influx of Th1 and CD8 cells in preeclampsia compared to non-pregnant women.…”
Section: Lymphocyte Activation and Potassium Channels In Healthy Pregcontrasting
confidence: 41%
“…The development of a maternal systemic inflammatory response has also been described in PE (Saito et al, 2007). An important feature of this disorder is the absence of Th2 skewness and thus the predominance of pro-inflammatory cytokines, as shown by a number of investigations (Darmochwal-Kolarz et al, 2002;Rein et al, 2002;Saito et al, 1999).…”
Section: Lymphocyte Activation and Potassium Channels In Healthy Pregmentioning
confidence: 98%
“…Like neopterin, IL-2R typically is elevated during allograft rejection and the development of certain malignancies, infectious diseases, and autoimmune disorders (24). IL-2, which is an important cytokine in the T-cell pathway, is increased in preeclampsia (2,25,26). The source of the Th1 cytokine may be decidual leukocytes and placenta (27).…”
Section: Discussionmentioning
confidence: 98%